PREDIKSI EROSI DAN PERENCANAAN KONSERVASI TANAH DAN AIR DI DAERAH ALIRAN SUNGAI PAKERISAN PROVINSI BALI - Ni Wayan Suprianingsih; I Wayan Sandi Adnyana; I Wayan Diara (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2023)
Pakerisan watershed is one of the watershed that has not followed the rules of soil and water conservation. This can destroy soil aggregates and cause high erosion. This study aims to predict the level of erosion and to plan soil and water conservation. Erosion prediction uses the USLE (Universal Soil Loss Equation). The prediction erosion showed that erosion is classified from slight to severe. The erosion rate is very light covering an area of 6,426.26 ha (71.28%) with natural forests, dryland agriculture, and paddy fields. The moderate erosion rate is 583.83 ha (6.48 %) on dryland and paddy fields farming. The severe erosion rate is 1,087.99 ha (12.07%) on land use in the form of dryland agriculture. The very severe erosion covering an area of 916.85 (10.17%) with the use of dryland agriculture. Conservation planning can be carried out by increasing vegetation density, adding mulch and conservation measures of making terraces with good construction. Keywords: Soil; Prediction Erosion; Conservation; Watershed